FORMATION OF THE SYSTEM OF ASSESSMENTS OF THE FINANCIAL AND INVESTMENT POTENTIAL OF AN ENTERPRISE - G. V. Strokovych; O. P. Mykolenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2018)
Based on the analysis of literary sources and based on the research objective it is suggested to group the evaluation indicators in the following directions: indicators of profitability, indicators of market activity, indicators of liquidity, indicators of capital structure (financial stability).